Mythic Resonance in the Modern Spectacle: Reimagining the Hero’s Awakening in Aladdin (2019) - Baral, Pabitra Raj (SCHOLARS: Journal of Arts & Humanities, 2025)
This research article explores how Disney’s live-action Aladdin (2019) reimagines the Arabian folktale through modern cinematic innovations while preserving its mythic core. Building on previous studies of ethical, psychoanalytic, and structural aspects of the film, this study fills a gap by examining the mythic resonance of Aladdin’s heroic journey and transformation, culminating in an awakening toward selfless service to humanity. Particularly, it scrutinizes how the film blends the Hero’s Journey motif with innovative techniques such as CGI, character development, and narrative restructuring to appeal to contemporary audiences and convey timeless values. Employing a qualitative research design, an interpretive approach, and a textual analysis, the study draws upon Joseph Campbell’s monomyth and Allison and Goethals’s model of psychological transformation, further informed by Vogler and Winkler’s insights on mythic adaptation in cinema. Findings reveal that the film’s cinematic enhancements, rather than eroding the mythic structure, help preserve it by tracing Aladdin’s journey from street thief to selfless hero, resulting in a psychological rebirth. Thus, the mythic core resonates even when repackaged through innovative spectacle in the film. This article contributes to myth studies and cinematic adaptation by highlighting the enduring power of mythic storytelling to engage audiences across cultures and time.